(3COH GdbVGAs - (3GHf CHj GdOe , EHQGgje Hf YHO Gddg Hf YHO GdefYe GdgePGfj GdMehj, GHf CHj GdOe,J (B642 (3g` s
(3ChdgG (B:s
(3hHYO aChdi eG CYedJ ajg GdbQGjM hoYdbJ Hg GdCacGQ GddhGbM gh Yde aQhY GdTQjYI s
(3BNQgG (B:s
(3aEf gPG GdcJGH bdjd ef cKjQ dGjhj GdYGde ef GdEMGWI HgG hMSHfG Gddg hfYe Gdhcjd s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B49 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B53s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCgdjI HHGQjS (B(996) s
Keywords: (3Gdabg GdTGaYjs